Efficacy of Calcium Channel Blocker as A Tocolytic Agent - SHAMAYELA H ASIFA A, SAADIA S (Journal of Fatima Jinnah Medical University, 2018)
Objective: This study was planned to determine the efficacy of calcium channel blocker as a tocolytic agent in pre-term labour and to evaluate the frequency of adverse effects of the drug Study design: Descriptive cross-sectional study Place and duration of study: Department of Obstetrics and Gynaecology. Fatima Memorial Hospital from March 2011 to August 2011 Sampling technique: Non-probability convenient sampling Method: All pregnant women irrespective of booking status, age and parity presenting with preterm labour with cervical dilatation less than 3 cm between 28 to 36 weeks with singleton and twin pregnancy and intact membranes were included in the study. A proforma was formulated to document the details of each patient. Nifedipine was started as a tocolytic agent in these patients. The efficacy of the drug to postpone the delivery was recorded and both major and minor side effects were observed. Results: During the study period 46 patients were enrolled. Delivery was successfully delayed upto 48 hours in 9 patients(19.5%) cases. Twenty seven cases (58.6%) delivered between 48 hours to 7 days. Thirteen cases (28.2%) remained undelivered till 7 days. Ca channel blocker failed to prolong pregnancy in 8.6% cases. Minor side-effects of the drug were observed in 5 cases (2.3%) like headache, nausea hypotension and flushing. No major serious adverse effect was seen in any women. Conclusion: Results of our study are highly encouraging for the use of nifedipine as tocolytic agent. It is safe and effectively prolongs pregnancy. It was associated with few minor side effects which were tolerable.